2019
DOI: 10.1002/aqc.3259
|View full text |Cite
|
Sign up to set email alerts
|

Nursery habitat for Asian horseshoe crabs along the northern Beibu Gulf, China: Implications for conservation management under baseline gaps

Abstract: Identification, protection and enhancement of essential habitats are priority issues for management and restoration of exploited species. The shores utilized by Asian horseshoe crabs as nurseries were surveyed and the coastal habitat characteristics were described in the northern Beibu Gulf of China. Regression models were applied to explore species‐habitat relationships. Fourteen and ten nursery sites were identified for Tachypleus tridentatus and Carcinoscorpius rotundicauda populations, respectively. Xiacun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Rudloe (1981) observed a gradual offshore movement of juvenile L. polyphemus to the deeper waters as they age. However, no such movement pattern was observed for juvenile T. tridentatus either on Kinmen Island, Taiwan, China (Chen et al 2004) or in the northern Beibu Gulf, China (Xie et al 2020), possibly due to the flat topography of the shores. Adult horseshoe crab populations exhibited contrasting migration patterns throughout their range.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Rudloe (1981) observed a gradual offshore movement of juvenile L. polyphemus to the deeper waters as they age. However, no such movement pattern was observed for juvenile T. tridentatus either on Kinmen Island, Taiwan, China (Chen et al 2004) or in the northern Beibu Gulf, China (Xie et al 2020), possibly due to the flat topography of the shores. Adult horseshoe crab populations exhibited contrasting migration patterns throughout their range.…”
Section: Introductionmentioning
confidence: 89%
“…Larvae are transported to and forage on the adjacent sheltered beaches for 7 years or longer (Seino et al 2000;Cheng et al 2015). Nursery habitat for C. rotundicauda is associated with mangroves and mudflats (Xie et al 2020), while the juveniles of other 3 species are found on sandy-mudflats where meiofaunal and infaunal prey are abundantly found (Hsieh & Chen 2009;Cheng et al 2015). T. tridentatus and L. polyphemus molt approximately 16 times in 10-14 years, whereas, T. gigas and C. rotundicauda molt around 13 times in 10 years until adulthood is reached (Sekiguchi et al 1988;Walls et al 2002;Hu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be attributed to the lack of important factors explaining the habitat characteristics of the target species [ 59 ]. For example, biotic and abiotic factors, such as sediment condition, density of prey, and coverage of seagrass patches, affect the distribution of the juveniles [ 20 , 21 , 60 ]. The sediment condition, which is one of the factors affecting juvenile distribution, can be estimated with further development of the UAV-SfM technique [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The revised "List of key protected wild animals in China" in 2021 officially listed tri-spine horseshoe crab as the second-class national protected wild animal. Current studies on horseshoe crab mainly focus on population survey (Xie et al, 2019), resource conservation (Zhu et al, 2020), artificial breeding (Tinker-Kulberg et al, 2020), blood collection (John et al, 2011;Owings et al, 2019), and recombinant Tachyplesin (Yu et al, 2020). The impact of environmental factors on horseshoe crabs is mainly concentrated on heavy metals, salinity, temperature, and sediments (Kwan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%